Effect of Vascular Risk Factors and Diseases on Mortality in Individuals with Dementia: A Systematic Review and Meta‐Analysis. Issue 1 (21st December 2015) - van de Vorst, Irene E.; Koek, Huiberdina L.; de Vries, Rehana; Bots, Michiel L.; Reitsma, Johannes B.; Vaartjes, Ilonca
Abstract : Objectives: To assess the effect of cardiovascular diseases and risk factors on mortality in individuals with dementia. Design: Systematic review and meta‐analysis. English‐ and Dutch‐language studies in PubMed, EMBASE, and PsycINFO databases were searched in April 2014 with hand‐searching of in‐text citations and no publication limitations. Inclusion criteria were original studies reporting on cardiovascular risk factors or diseases and their relationship with survival in individuals with dementia. The Quality In Prognosis Studies tool was used to appraise all included articles. Setting: Population‐, hospital‐, and nursing home–based. Participants: Community‐dwelling, hospitalized individuals and nursing home residents with dementia. Measurements: A random‐effects meta‐analysis was performed to investigate the effect of several cardiovascular diseases and risk factors on overall mortality. Results: Twelve studies with 235, 865 participants were included. In pooled analyses, male sex (hazard ratio (HR) = 1.67, 95% confidence interval (CI) = 1.56–1.78), diabetes mellitus (DM) (HR = 1.49, 95% CI = 1.33–1.68), smoking (ever vs never) (HR = 1.37, 95% CI = 1.17–1.61), coronary heart disease (CHD) (HR = 1.21, 95% CI = 1.02–1.44) and congestive heart failure (CHF) (HR = 1.37, 95% CI = 1.18–1.59) were associated with mortality. Stroke, high blood pressure, being overweight, and hypercholesterolemia were not statistically significantly related to mortality. Conclusion: Individuals with dementia and DM, smoking, CHD, and CHF have a greater risk of death than individuals with dementia without these risk factors or diseases.